Ragam Deiksis Pesona dan Waktu dalam Cerpen Smokol Karya Nukila Akmal - Nurul Kholiza; Moh Jailani (Lembaga Pengembangan Kinerja Dosen, 2024)
Deixis is a field of pragmatic study that discusses the relationship between language structures. and where the language is spoken. The use of the term